Childhood intussusception: A prospective study of management trend in a developing country - Olakayode Olaolu Ogundoyin; Dare Isaac Olulana; Taiwo Akeem Lawal (Wolters Kluwer Medknow Publications, 2015)
Background: The management of intussusception has evolved universally from the use of hydrostatic reduction through operative reduction to the use of pneumatic reduction for the acute and uncomplicated cases and surgical reduction for the complicated cases. However, the process of evolution has been very slow in the developing countries, especially sub-Saharan Africa, due to lack of requisite facilities and expertise to manage these patients nonoperatively. This study examined the trends in the management of childhood intussusception in a developing country, compared operative and nonoperative modalities of treatment, and assessed the impact of delayed presentation on the outcome of management. Patients and Methods: This was a prospective study of the management of children with intussusception at the University College Hospital, Ibadan, Nigeria. Results: Fifty-five consecutive cases of intussusception that presented to the Children Emergency Unit of the University College Hospital between January 2005 and December 2011 were prospectively studied. Details of sex, age of the patients, clinical presentation, duration of symptoms, mode of treatment, and incidence of recurrence were recorded and analyzed. The median age was 7 months. Moreover, the duration of symptoms varied from 1 to 21 days with a mean of 4 days. Twenty-two patients (40%) had attempted hydrostatic reduction; this was successful in 14 patients (63.6%), whereas 8 patients (36.4%) had failed reduction. In all, 41 patients (74.6%) had operative management of intussusceptions; primary operative intervention was carried out in 33 patients (60%) and secondary surgical management in 8 patients (14.5%) with failed hydrostatic reduction. At surgery, manual reduction of intussusception was carried out on 17 patients (30.9%) and resection of devitalized bowel with end to end anastomosis was carried out on the remaining 24 patients (43.6%). The incidence of surgical intervention for intussusception was 74.6%, mortality was 3.6%, and recurrence rate was 3.6%. Conclusions: Nonoperative management of intussusception should be adopted in carefully selected cases of intussusception in this subregion as it will help to reduce the financial burden on the parents while surgical management should be reserved for the complicated cases.